Education about stunting prevention with knowledge of pregnant women at the ritnawati midwife clinic, Pantai Cermin district, Serdang Bedagai district, year 2022 - Rapida Saragih; Linda Hernike Napitupulu; Christin Jayanti (Science Midwifery, 2023)
Stunting or often called stunted or short according to Umar 2017 said that the condition of failure to thrive in children under five years old (toddlers) is due to chronic malnutrition and repeated infections, especially during the first 1,000 Days of Life (HPK) period. To knowEducation about Stunting Prevention on Knowledge of Pregnant Women. The research design used isquasi experimental research (quasi experimental). The population in this study were all pregnant women. The sampling technique was purposive sampling, namely sampling using certain considerations in accordance with the desired criteria to be able to determine the number of samples to be studied, amounting to 30 respondents. Data analysis used univariate analysis using frequency distribution and bivariate analysis using paired t test. Research is known from the test resultstest paired t test where the results of the study the average knowledge score on the pre-test with no treatment was 11.40, whereas after the knowledge treatment was done withEducation about stunting preventionhas an average knowledge score on the post test, namely 12.97, meaning that it can be concluded that knowledge isEducation about stunting prevention after treatment can increase respondents' knowledge about stunting. Based on the results of the study it can be concluded thatknowledge withEducation aboutafter the treatment can increase the knowledge of respondents aboutStunting prevention. Expectedknowledge withEducation aboutafter the treatment can increase the knowledge of respondents aboutStunting prevention.